Identification of key microRNAs affecting melanogenesis of breast muscle in Muchuan black-boned chickens by RNA sequencing. Issue 3 (3rd May 2020) - Yu, S.; Wang, G.; Liao, J.; Tang, M.; Chen, J.
ABSTRACT: 1. Melanin content is considered an important indicator of meat quality in black-boned chickens, which have a high market value. To understand the complex physiological processes underlying muscle melanogenesis in this chicken, differentially expressed miRNAs (DEMs) were detected between black muscle (BM) and white muscle (WM) of chickens using high-throughput sequencing technology. Six small RNA libraries were constructed, and more than 16.75 million clean reads were obtained for each library. 2. A total of 582 known miRNAs and 65 novel miRNAs were identified from the six chicken sequence libraries. A total of 19 DEMs were identified between the two groups, of which nine were upregulated and 10 were downregulated. Furthermore, the DEMs were predicted to target 572 genes. 3. Certain DEMs (such as miR-204, miR-133b, and miR-12 229-3p) and their target genes may play an important role in muscle melanogenesis of chickens. These findings provide a foundation for clarifying the miRNA regulatory mechanisms involved in muscle pigmentation in avian species.